EFEKTIVITAS MODEL PEMBELAJARAN EKONOMI BERBASIS PROBLEM BASED LEARNING DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS XI-A SMA KRISTEN PALANGKA RAYA - Tina Tina; Eriawaty Eriawaty; Dewi Rakhmawati (Jurnal Pendidikan Ekonomi (JURKAMI), 2025)
Critical thinking is one of the skills that needs to be developed in the economics learning process at the high school level. However, in reality, this ability has not been optimally developed among students at Palangka Raya Christian High School. This condition is evident in students' poor communication skills during learning activities, such as a lack of active participation, low courage in expressing opinions, and a weak ability to respond logically to others' ideas. This situation indicates that students are not yet fully able to process, evaluate, and express information critically, which are actually the main indicators of critical thinking.This study aims to comprehensively analyze students' communication skills in economics learning activities and identify the role of teachers in building a communicative and adaptive learning environment. This study uses a qualitative approach with a case study method, where the primary data is obtained through in-depth interviews and participatory observations of teachers and grade XI-A students in economics subjects at Palangka Raya Christian High School, while secondary data is collected from literature studies and previous research; the data analysis process is carried out through the stages of systematic collection, reduction, presentation, and drawing conclusions. The findings of this study indicate that although teachers have provided an interactive forum through group discussions, questions and answers, and presentations supported by digital media, there is still a disparity in communication courage among students which is influenced by psychological factors, individual abilities, and limited time and learning instruments.